Factors affecting determining the direction of urban growth in the city of Baquba (Journal of the College of Basic Education, 2022)
The research seeks to identify the factors affecting the direction of the urban growth of the city of Baquba and its duration from 1970 to the end of 2019 where natural and human factors affecting the direction of urban growth in the city were studied in addition to identifying future directions for urban growth in the light of the city's population increase, which would Increase the appearance of new housing units.